Al-tic intermediate alloy with high content of tic and preparation method thereof

CN122669256BActive Publication Date: 2026-10-20CENT SOUTH UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611161988.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-08-03
Publication Date
2026-10-20
Estimated Expiration
2046-08-03

AI Technical Summary

Technical Problem

[0005]本发明旨在解决现有SHS法制备高TiC含量的Al-TiC中间合金时存在的以下技术问题:1)SHS起爆过早致反应不均及Al3Ti残留;2)TiC/Al润湿性差致偏聚团聚;3)原位合成TiC易粗化;4)需过高铝熔温(>900℃)引发反应等技术问题

Benefits of technology

[0025]1)本发明方法中的SHS起爆时机精确可控:通过在CuO表面磷化形成Cu3P/CuO梯度缓释壳,使Al-CuO铝热反应延迟至预制块被铝液完全浸润、温度场均匀后发生,避免因过早爆燃导致的反应不均、Ti未完全碳化生成Al3Ti及局部过热,从根源上消除粗大Al3Ti相(XRD未检出);

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122669256B_ABST
    Figure CN122669256B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of metal matrix composite and intermediate alloy preparation, and particularly discloses an Al-TiC intermediate alloy with high TiC content and a preparation method thereof. The application utilizes CuO powder to form a Cu3P / CuO gradient slow-release shell through surface phosphorization of sodium hypophosphite to accurately delay the SHS initiation time, utilizes Mg-Sc composite wetting agent to reduce the TiC / Al interface energy, utilizes additional nano TiC particles to dilute the in-situ reaction heat to inhibit coarsening, utilizes an inert atmosphere gradient pressure heat pressing preform block, and utilizes an electromagnetic stirring coupled ultrasonic dispersion method, so that the Al-TiC intermediate alloy with high TiC content and without Al4C3 and coarse Al3Ti phase and with TiC dispersed distribution is prepared at a lower external melting temperature by controlling the SHS initiation time, improving the TiC / Al wettability, and inhibiting TiC coarsening and segregation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of metal matrix composite materials and master alloy preparation technology, and in particular to an Al-TiC master alloy with high TiC content and its preparation method. Background Technology

[0002] TiC particles are an important candidate for preparing aluminum-based particle-reinforced materials and other metal-based particle-reinforced materials. Preparing Al-TiC master alloys with high TiC mass fraction is an important direction for current development. It can solve the drawbacks of insufficient wettability of TiC particles when directly added, resulting in low yield, poor mechanical properties of the particle / matrix interface, and harmful interfacial reactions.

[0003] Currently, the mainstream preparation methods for Al-TiC master alloys mainly include: ① Melt reaction method: using K2TiF6 as the titanium source and graphite or carbon nanotubes as the carbon source, TiC is synthesized by reaction in aluminum melt at 1150~1250℃; however, the TiC content of this method is usually <15wt%, and it is easy to introduce fluoride salt inclusions and harmful Al4C3 phase, making it impossible to prepare master alloys with high TiC mass fraction. ② Conventional self-propagating high-temperature synthesis (SHS) method: Ti, C, Al and exogenous powders (such as CuO powder, Mg powder) are mixed and pressed into aluminum melt at 760~820℃, and Ti+C→TiC is ignited by Al-CuO exothermic reaction or external heating. However, this method has the following problems: the timing of the SHS reaction explosion is uncontrollable, and the explosion occurs before the pre-formed block is fully wetted, resulting in uneven reaction and unreacted Ti agglomeration to form coarse Al3Ti intermetallic compounds; when the TiC content is high (>30wt%), TiC particles are severely agglomerated and segregated along the grain boundaries, and cannot be uniformly distributed; in addition, the wetting angle between C and Al melt is large (>90°), and although adding Mg alone can reduce the wetting angle, it is still not enough to make ≥50wt% TiC stably dispersed in the Al matrix; in addition, simple in-situ synthesis easily leads to TiC grain growth and coarsening.

[0004] Therefore, it is urgent to propose a new preparation process for Al-TiC master alloys with high TiC content in order to overcome the current technical defects in this field and prepare high-quality Al-TiC master alloys with high TiC content. Summary of the Invention

[0005] The present invention aims to solve the following technical problems in the preparation of Al-TiC master alloys with high TiC content by the existing SHS method: 1) premature SHS detonation leading to uneven reaction and Al3Ti residue; 2) poor TiC / Al wettability leading to segregation and agglomeration; 3) easy coarsening of TiC in situ synthesis; 4) the need for excessively high aluminum melting temperature (>900℃) to initiate the reaction, etc. Therefore, this invention provides a method for preparing an Al-TiC master alloy with high TiC content. This invention utilizes a comprehensive technical solution of "CuO powder phosphating with sodium hypophosphite to form a Cu3P / CuO gradient slow-release shell to precisely delay the SHS detonation timing + Mg-Sc composite wetting agent to reduce TiC / Al interfacial energy + external addition of nano-TiC particles to dilute in-situ reaction heat to suppress coarsening + Ar atmosphere gradient pressure hot pressing preform + electromagnetic stirring coupled with ultrasonic dispersion". This method achieves the preparation of an Al-TiC master alloy ingot with high TiC content, free of Al4C3 and coarse Al3Ti phases, and with dispersed TiC distribution, at a relatively low external melting temperature (≤800℃) by controlling the SHS detonation timing, improving TiC / Al wettability, and suppressing TiC coarsening and segregation.

[0006] In a first aspect, the present invention provides a method for preparing an Al-TiC master alloy with high TiC content, comprising the following steps:

[0007] S1. CuO powder is added to sodium hypophosphite solution, heated and impregnated, filtered, dried and calcined to obtain CuO slow-release microparticles with a Cu3P / CuO gradient slow-release shell on the surface.

[0008] S2. Mix Ti powder and C powder at a mass ratio of (4~4.5):1 to obtain a mixed powder. Weigh 40~50 parts of the mixed powder, 45~55 parts of nano TiC powder, 3~5 parts of CuO slow-release particles, 1~2 parts of composite wetting agent and 40~50 parts of Al powder by mass, and mix them to obtain the precursor powder.

[0009] S3. The precursor powder is ball-milled and mixed under an inert atmosphere, placed in a mold, pre-pressurized and degassed, then heated to 110~130℃ and pressurized to 130~150Mpa, held under pressure to form, and dried to obtain a reaction preform.

[0010] S4. Place the reaction preform into the aluminum melt, react for 40-60 seconds, and then apply electromagnetic stirring and ultrasonic vibration treatment to the molten system. After treatment, cast the melt, cool it, demold it, and anneal it to obtain an Al-TiC master alloy with high TiC content.

[0011] According to some embodiments of the present invention, the TiC content in the Al-TiC master alloy is 50wt%~58wt%.

[0012] According to some embodiments of the present invention, in step S1, the particle size of the CuO powder is 5~8μm; the sodium hypophosphite solution is an aqueous solution of sodium hypophosphite with a concentration of 0.25~0.7mol / L.

[0013] According to some embodiments of the present invention, in step S1, the heating and impregnation temperature is 70~90℃ and the time is 20~40min; the calcination temperature is 300~350℃; and the thickness of the Cu3P / CuO gradient slow-release shell is 0.1~0.5μm.

[0014] This invention utilizes CuO powder impregnated in a sodium hypophosphite aqueous solution, followed by heating, drying, and calcination to form a Cu3P / CuO gradient slow-release shell on the surface of CuO particles, thus obtaining CuO slow-release particles. This method effectively solves the problems of uneven reaction and Al3Ti residue caused by the direct exothermic reaction of CuO addition leading to SHS explosion. It ensures that TiC particles are synthesized along the Ti(s) + C(s) → TiC reaction pathway, rather than the pathways 3C + 4Al → Al4C3, 3Al3Ti + Al4C3 → 3 TiC + 13Al, or Al3Ti + C → TiC + 3Al. The former produces fine and uniform TiC particles, while the latter not only generates Al3Ti in the matrix, reducing the TiC particle content in the finished product, but also generates the harmful Al4C3 phase, lowering product quality. Furthermore, the generated TiC particles are larger and more prone to agglomeration, making subsequent dispersion more difficult.

[0015] According to some embodiments of the present invention, in step S2, the average particle size of the nano-TiC powder is ≤2μm; the composite wetting agent includes Mg powder and Sc powder, wherein the mass ratio of Mg to Sc is (5~8):1.

[0016] In the precursor formulation of this invention, a certain proportion of added nano-TiC powder is used as diluent particles, and Mg and Sc elements are used as wetting agents for doping. This has the following effects: ① It can further reduce the difficulty of generating a sufficient mass fraction of TiC in situ in the target product, and can effectively improve the dispersibility of the in-situ generated TiC particles; ② In the method of this invention, there is free Ti in the aluminum melt, which easily forms a titanium-rich layer or a thin shell structure of L12-Al3Ti on the surface of TiC particles under high temperature conditions, solving the drawbacks of poor TiC absorption rate caused by wetting of TiC particles with Al melt and weak mechanical properties at the interface with Al matrix after introduction; ③ By introducing Mg elements, local high temperature is generated during molten casting to promote the synthesis of Ti(s) + C(s) → TiC reaction pathway without raising the overall melt temperature. Furthermore, due to the presence of Sc elements, the surface state of C elements is further improved, increasing the probability of direct solid-solid reaction with Ti elements to generate fine and dispersed TiC particles.

[0017] According to some embodiments of the present invention, in step S3, the ball milling conditions are: planetary ball milling at a speed of 180~250 rpm for 8~15 min; the pre-pressure exhaust pressure is 45~60 MPa; the pressure is applied at a rate gradient of 5~10 MPa / min; and the pressure holding and molding time is 2~5 min.

[0018] According to some embodiments of the present invention, in step S4, the temperature of the aluminum melt is 760~795℃; the mass ratio of the reaction preform to the aluminum melt is (4~5):1.

[0019] According to some embodiments of the present invention, in step S4, the frequency of the electromagnetic stirring treatment is 30~50Hz and the time is 4~6min; the frequency of the ultrasonic vibration treatment is 20kHz, the power is 300~500W, and the time is 2~3min.

[0020] Because the high-quality TiC particles of this invention produce aluminum melt with extremely high viscosity, excessive viscosity during the casting process can lead to problems such as casting failure and uneven distribution of TiC particles. Electromagnetic stirring effectively stimulates the macroscopic movement of the melt in the crucible, preventing TiC particles from settling and agglomerating due to their specific gravity. Ultrasonic vibration, on the other hand, excites the interaction between atoms at the interface between TiC particles and Al melt from a microscopic perspective, improving the surface polarity of TiC particles and the wetting properties between them and the Al melt. The combined effect of these two techniques, along with the aforementioned technical means, effectively solves the problems of TiC particle dispersion and poor wettability.

[0021] According to some embodiments of the present invention, in step S4, the annealing treatment is homogenization annealing at 410~440°C for 6~8 hours.

[0022] This invention also utilizes the difference in high-temperature stability between TiC particles and by-product impurity phases such as Al3Ti and Al4C3 to perform homogenization annealing at a suitable temperature, thereby incorporating the non-target phases into the aluminum matrix through solid solution, reducing the disadvantages caused by such non-target phases in the subsequent direct preparation of related finished products or as intermediate alloy additions.

[0023] In a second aspect, the present invention provides an Al-TiC master alloy with high TiC content, wherein the Al-TiC master alloy with high TiC content is prepared by the preparation method described in the first aspect of the present invention; wherein the TiC content in the Al-TiC master alloy is 50wt%~58wt%.

[0024] The beneficial effects of this invention are:

[0025] 1) The SHS initiation timing in the method of this invention is precisely controllable: by forming a Cu3P / CuO gradient slow-release shell by phosphating the CuO surface, the Al-CuO aluminothermic reaction is delayed until the preform is completely wetted by the aluminum liquid and the temperature field is uniform, thus avoiding uneven reaction caused by premature deflagration, incomplete carbonization of Ti to form Al3Ti and local overheating, and eliminating coarse Al3Ti phase from the root (not detected by XRD).

[0026] 2) This invention achieves good wetting and dispersion distribution even with high TiC content: by using Mg adsorption at the TiC / Al interface to reduce surface energy, and Sc atom segregation on the surface of TiC particles further reduces the TiC / Al contact angle from 55~60° treated with pure Mg to ≤40° (measured 34~39°), overcoming the inherent problem of poor wetting of high volume fraction ceramic phases in aluminum matrix. Combined with the addition of nano-TiC to provide heterogeneous nucleation sites to inhibit excessive growth of in-situ TiC;

[0027] 3) The method of this invention can suppress TiC coarsening and segregation: by adding 45~55wt% nano-TiC dilution particles to absorb the heat of SHS reaction, the in-situ TiC synthesis can be carried out under controlled temperature rise, and the grain size can be stabilized at the submicron level (0.5~1.2μm); the gradient hot pressing preform is used to improve the uniformity and permeability of the green body and reduce the source of component segregation; and the subsequent electromagnetic + ultrasonic dual-frequency dispersion completely breaks the residual agglomeration.

[0028] 4) The method of this invention can prepare high TiC ingots at low melting temperatures: using CuO aluminothermic assisted combustion, the aluminum melt only needs 760~795℃ (100~150℃ lower than the traditional SHS which requires 850~950℃), resulting in low energy consumption and reduced aluminum melt gas absorption and oxidation; moreover, the final product has a TiC mass fraction of 50~58wt%, no Al4C3 brittle phase, and an ingot density ≥98%, which can be directly used as a high-concentration master alloy for mass production of refining agents or composite materials;

[0029] 5) The present invention has strong process adaptability: the parameters have wide windows (CuO shell thickness, Mg-Sc ratio, amount of added TiC, and gradient pressure range are clearly defined), which is suitable for industrial scale-up, unlike the simple laboratory SHS ignition mode of traditional methods.

[0030] Other features and advantages of the invention will be set forth in the description which follows, and will be apparent in part from the description, or may be learned by practicing the invention. Attached Figure Description

[0031] The present invention will be further described below with reference to the accompanying drawings and embodiments, wherein:

[0032] Figure 1 This is a scanning electron microscope image of the Al-TiC master alloy from Example 1 of the present invention;

[0033] Figure 2 Here is a scanning electron microscope image of the Al-TiC master alloy of Comparative Example 1 of this invention;

[0034] Figure 3 This is a scanning electron microscope image of the Al-TiC master alloy of Comparative Example 4 of the present invention. Detailed Implementation

[0035] The following will describe the concept and technical effects of the present invention clearly and completely with reference to embodiments, so as to fully understand the purpose, features and effects of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are all within the scope of protection of the present invention.

[0036] Unless otherwise specified in the examples, the procedures should be performed under standard conditions or conditions recommended by the manufacturer. Reagents or instruments whose manufacturers are not specified are all commercially available products.

[0037] Example 1

[0038] This embodiment provides a method for preparing Al-TiC master alloys with high TiC content. The specific steps are as follows:

[0039] 1) Preparation of CuO sustained-release microparticles:

[0040] CuO powder (average particle size 7 μm) was immersed in a 0.45 mol / L NaH2PO2 aqueous solution, heated to 80℃, and immersed for 30 min. After filtration, it was dried in an oven at 120℃, then heated to 320℃ and calcined for 15 min to form a Cu3P / CuO gradient slow-release shell with a thickness of 0.2~0.3 μm on the surface of CuO particles, thus obtaining CuO slow-release particles.

[0041] 2) Precursor ingredients:

[0042] Weigh 208g of Ti powder (average particle size 39.6μm) and 52g of C powder (average particle size 0.7μm) and mix them (Ti:C mass ratio is 4:1). Then weigh 292g of added nano TiC powder (average particle size 1.5μm) diluent particles, 23g of CuO slow-release microparticles, and 9.4g of Mg-Sc composite wetting agent (Mg:Sc mass ratio is 6:1, Mg powder average particle size is 13μm, and Sc powder average particle size is 8μm). Finally, add 260g of Al powder (average particle size 33.5μm) and mix to obtain the precursor powder.

[0043] 3) Precast block forming:

[0044] The precursor powder was mixed by planetary ball milling at 220 rpm for 12 min under an argon atmosphere. The mixed precursor powder was then placed in a mold, and the pore gas was first pre-pressed at 50 MPa to remove it. The mold was then heated to 120 °C and pressurized at a rate gradient of 8 MPa / min to 140 MPa. After holding the pressure for 3 min, the mold was demolded and dried at 120 °C for 24 h to obtain the reaction preform.

[0045] 4) Melt SHS reaction:

[0046] 188g of industrial pure Al was melted, superheated to 782℃, and kept at this temperature for deoxidation and slag removal. The reaction preform was preheated to 180℃ and then pressed into the molten aluminum. The CuO slow-release shell was completely wetted by the molten aluminum in the preform and the temperature became uniform. After this, it ruptured, triggering the Al-CuO aluminothermic reaction and releasing heat. This caused the local SHS temperature to reach approximately 1170℃, triggering the thermal explosion mode: Ti+C→TiC in-situ synthesis. At the same time, nano-TiC powder was added to dilute and absorb the heat of reaction.

[0047] 5) Dual-frequency dispersion:

[0048] Step 4) After reacting for 50 seconds, observe the surface of the melt to show a bright flash, and then stabilize, indicating that the reaction is complete. Then apply electromagnetic stirring (frequency 42Hz, time 5min) to homogenize the melt. Then superimpose ultrasonic vibration (frequency 20kHz, power 350W, time 2.5min) to break up TiC agglomerates and promote TiC wetting and spreading into the aluminum matrix.

[0049] 6) Casting and annealing:

[0050] The melt was poured into a metal mold preheated to 300°C, cooled and demolded, and then homogenized and annealed at 420°C for 7 hours. After air cooling, Al-TiC master alloy ingots were obtained.

[0051] The Al-TiC master alloy ingot obtained in this embodiment was tested, and the results are as follows:

[0052] The scanning electron microscope image of the Al-TiC master alloy is as follows: Figure 1 As shown, metallographic and SEM images reveal that TiC particles are uniformly dispersed without grain boundary agglomeration; XRD analysis results show no A. l4 C3 and Al3Ti peaks; chemical analysis showed that the TiC mass fraction was approximately 55.2 wt%, and the average TiC particle size was approximately 1.2 μm; the apparent contact angle of TiC / Al was approximately 34° (seat drop method); the ingot density was ≥98.5%.

[0053] Example 2

[0054] This embodiment provides a method for preparing Al-TiC master alloys with high TiC content. The preparation method in this embodiment is the same as that in Example 1, except that some process parameters are adjusted:

[0055] In this embodiment, step 1) uses a 0.3 mol / L NaH2PO2 aqueous solution, CuO powder with a particle size of 5 μm, calcination temperature of 300℃, and time of 20 min; step 2) adds 45 wt% nano-TiC powder, 1 wt% Mg-Sc composite wetting agent, with a Mg to Sc mass ratio of 5:1, and 3 wt% CuO slow-release particles; step 3) applies gradient pressure to 130 MPa; step 4) melts and superheats Al to 760℃; step 5) uses electromagnetic stirring at a frequency of 30 Hz for 6 min, ultrasonic vibration at a frequency of 20 kHz and a power of 300 W for 3 min; and step 6) annealing temperature of 410℃ for 8 h.

[0056] In the Al-TiC master alloy casting obtained in this embodiment, the TiC mass fraction is approximately 50.6 wt%, and there are no Al4C3 or Al3Ti phases, as well as an acceptable amount of slight micro-agglomeration.

[0057] Example 3

[0058] This embodiment provides a method for preparing Al-TiC master alloys with high TiC content. The preparation method in this embodiment is the same as that in Example 1, except that some process parameters are adjusted:

[0059] In this embodiment, step 1) uses a 0.6 mol / L NaH2PO2 aqueous solution, CuO powder with a particle size of 8 μm, calcination temperature of 340℃, and time of 10 min; step 2) adds 55 wt% nano-TiC powder, 2 wt% Mg-Sc composite wetting agent, with a Mg to Sc mass ratio of 8:1, and 5 wt% CuO slow-release particles; step 3) applies gradient pressure to 150 MPa; step 4) melts and superheats Al to 795℃; step 5) uses electromagnetic stirring at a frequency of 50 Hz for 4 min, ultrasonic vibration at a frequency of 20 kHz and a power of 500 W for 2 min; and step 6) annealing temperature of 440℃ for 6 h.

[0060] In the Al-TiC master alloy casting obtained in this embodiment, the TiC mass fraction is approximately 57.8 wt%, and the TiC is uniformly distributed without any harmful phases.

[0061] Comparative Example 1

[0062] This comparative example provides a method for preparing Al-TiC master alloy. This comparative example is basically the same as Example 1, except that CuO slow-release particles are not prepared in this comparative example. CuO powder is used directly instead of CuO slow-release particles in step 2). The remaining steps and process parameters are the same as in Example 1. Then, in step 4), the SHS is ignited the moment the preform is put into the aluminum liquid (782°C). The preform reacts violently before the center is completely wetted.

[0063] Ultimately, the product of this comparative example showed localized unreacted Ti cores, as shown in the scanning electron microscope image. Figure 2 As shown, XRD analysis detected obvious Al3Ti peaks and uneven TiC distribution with segregation bands. The measured TiC content in the intermediate alloy was only about 41wt% (part of the Ti was consumed to form Al3Ti).

[0064] Comparative Example 2

[0065] This comparative example provides a method for preparing Al-TiC master alloy. This comparative example is basically the same as Example 1, except that in step 2) of this comparative example, only Mg powder (1.6wt%) is used as a wetting agent; the remaining steps and process parameters are the same as those in Example 1.

[0066] Ultimately, in the Al-TiC master alloy prepared in this comparative example, the TiC / Al contact angle was approximately 58°. TiC particles exhibited a network-like segregation along the primary α-Al grain boundaries. After ultrasonication, a small amount of agglomeration remained. XRD analysis showed no Al4C3, but trace amounts of Al3Ti were present (due to local enrichment of Ti). The actual TiC content was approximately 53 wt%, but the microstructure was poorly uniform.

[0067] Comparative Example 3

[0068] This comparative example provides a method for preparing Al-TiC intermediate alloy. This comparative example is basically the same as Example 1, except that in step 2) of this comparative example, nano TiC powder is not added externally, and Ti powder and C powder of equal mass are used instead.

[0069] In this comparative example, the excessively high SHS combustion wave temperature caused significant coarsening of TiC grains (the average size increased from about 1.2 μm in Example 1 to more than 2.5 μm), and local sintering agglomerates and increased segregation occurred. The measured TiC content was about 34 wt%, and the TiC mass fraction content in the product decreased.

[0070] Comparative Example 4

[0071] This comparative example provides a method for preparing Al-TiC intermediate alloy. This comparative example is basically the same as Example 1, except that ultrasonic vibration treatment is omitted in step 5) of this comparative example.

[0072] Scanning electron microscope (SEM) images of the Al-TiC master alloy prepared in this comparative example are shown below. Figure 3 As shown, it is evident that the secondary and tertiary TiC aggregates are not dispersed, and the TiC / Al interface is not sufficiently wetted, with some areas exhibiting "island-like" enrichment.

[0073] The embodiments of the present invention have been described in detail above. However, the present invention is not limited to the above embodiments. Within the scope of knowledge possessed by those skilled in the art, various changes can be made without departing from the spirit of the present invention. Furthermore, the embodiments of the present invention and the features thereof can be combined with each other unless otherwise specified.

Claims

1. A method for preparing an Al-TiC master alloy with high TiC content, characterized in that, Includes the following steps: S1. CuO powder is added to sodium hypophosphite solution, heated and impregnated, filtered, dried and calcined to obtain CuO slow-release microparticles with a Cu3P / CuO gradient slow-release shell on the surface. S2. Mix Ti powder and C powder at a mass ratio of (4~4.5):1 to obtain a mixed powder. Weigh 40~50 parts of the mixed powder, 45~55 parts of nano TiC powder, 3~5 parts of CuO slow-release particles, 1~2 parts of composite wetting agent and 40~50 parts of Al powder by mass, and mix them to obtain the precursor powder. S3. The precursor powder is ball-milled and mixed under an inert atmosphere, placed in a mold, pre-pressurized and degassed, then heated to 110~130℃ and pressurized to 130~150Mpa, held under pressure to form, and dried to obtain a reaction preform. S4. Place the reaction preform into the aluminum melt, react for 40-60 seconds, and then apply electromagnetic stirring and ultrasonic vibration treatment to the molten system in sequence; after treatment, cast the melt, cool and demold, and anneal to obtain the Al-TiC master alloy with high TiC content. In step S2, the average particle size of the nano-TiC powder is ≤2μm; the composite wetting agent includes Mg powder and Sc powder, wherein the mass ratio of Mg to Sc is (5~8):

1.

2. The method for preparing the Al-TiC master alloy with high TiC content according to claim 1, characterized in that, The TiC content in the Al-TiC master alloy is 50wt%~58wt%.

3. The method for preparing the Al-TiC master alloy with high TiC content according to claim 1, characterized in that, In step S1, the CuO powder has a particle size of 5~8μm; the sodium hypophosphite solution is an aqueous solution of sodium hypophosphite with a concentration of 0.25~0.7mol / L.

4. The method for preparing the Al-TiC master alloy with high TiC content according to claim 1, characterized in that, In step S1, the heating and impregnation temperature is 70~90℃ and the time is 20~40min; the calcination temperature is 300~350℃; and the thickness of the Cu3P / CuO gradient slow-release shell is 0.1~0.5μm.

5. The method for preparing the Al-TiC master alloy with high TiC content according to claim 1, characterized in that, In step S3, the ball milling conditions are as follows: planetary ball milling at a speed of 180~250 rpm for 8~15 min; the pre-pressure exhaust pressure is 45~60 MPa; the pressurization is applied at a gradient rate of 5~10 MPa / min; and the pressure holding and molding time is 2~5 min.

6. The method for preparing the Al-TiC master alloy with high TiC content according to claim 1, characterized in that, In step S4, the temperature of the aluminum melt is 760~795℃; the mass ratio of the reaction preform to the aluminum melt is (4~5):

1.

7. The method for preparing the Al-TiC master alloy with high TiC content according to claim 1, characterized in that, In step S4, the electromagnetic stirring treatment has a frequency of 30~50Hz and a duration of 4~6min; the ultrasonic vibration treatment has a frequency of 20kHz, a power of 300~500W, and a duration of 2~3min.

8. The method for preparing the Al-TiC master alloy with high TiC content according to claim 1, characterized in that, In step S4, the annealing process is homogenization annealing at 410~440℃ for 6~8 hours.

9. A high TiC content Al-TiC master alloy, characterized in that, The high TiC content Al-TiC master alloy is prepared by the preparation method according to any one of claims 1 to 8; the TiC content in the Al-TiC master alloy is 50wt% to 58wt%.

Citation Information

Patent Citations

  • Preparation method of nano-TiC-particle-reinforced aluminum matrix composite

    CN107502771A

  • Preparation method of reinforced copper-based electrical contact composite material based on carbon nanotubes

    CN119710341A